2014
DOI: 10.1155/2014/815495
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Ligninolytic Enzymes by a MushroomStereum ostrea

Abstract: The white rot fungi Stereum ostrea displayed a wide diversity in their response to supplemented inducers, surfactants, and copper sulphate in solid state fermentation. Among the inducers tested, 0.02% veratryl alcohol increased the ligninolytic enzyme production to a significant extent. The addition of copper sulphate at 300 μM concentration has a positive effect on laccase production increasing its activity by 2 times compared to control. Among the surfactants, Tween 20, Tween 80, and Triton X 100, tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
3
38
1
3
Order By: Relevance
“…Screening of wood decaying microbes have been phenomenal in exploring their properties of releasing extracellular enzymes which are responsible for delignification [32] isolated 58 bacterial isolates from effluent and soil sediment samples from chemically contaminated sites of Surat to screen for potential laccase producers [29] attempted to screen, optimize, production and partially purify laccase enzyme produced from consortium of laccase producing Pseudomonas aeruginosa and Pseudomonas fluorescens. White rot fungi have also been reported to possess lignolytic properties and notably effect of different inducers has also been explored for optimal laccase production [11,33]. Selvam et al [34].…”
Section: Screening Isolation and Identification Of Indigenous Laccasmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of wood decaying microbes have been phenomenal in exploring their properties of releasing extracellular enzymes which are responsible for delignification [32] isolated 58 bacterial isolates from effluent and soil sediment samples from chemically contaminated sites of Surat to screen for potential laccase producers [29] attempted to screen, optimize, production and partially purify laccase enzyme produced from consortium of laccase producing Pseudomonas aeruginosa and Pseudomonas fluorescens. White rot fungi have also been reported to possess lignolytic properties and notably effect of different inducers has also been explored for optimal laccase production [11,33]. Selvam et al [34].…”
Section: Screening Isolation and Identification Of Indigenous Laccasmentioning
confidence: 99%
“…and Fusarium sp [25]. Usha has studied the diversified effect of white rot fungi Stereum ostrea in their response to supplemented inducers, surfactants, and copper sulphate in solid state fermentation [11]. Copper as a micronutrient has a key role as a metal activator, induces both laccase transcription, and plays an important role in laccase production [17].…”
Section: Laccase Production By Bacterial Consortia Through Submerged mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, non-ligninolytic fungi are also credited for the extraction of very essential commercially important enzymes with wide applications in industrial segments like detergents, food, feed, pharmaceutical, and biofuels. Fungi would be more capable of producing certain enzymes with high productivity during SSF as compared to SmF [24]. Additionally, some bacteria are also known for the enzyme production through SSF.…”
Section: Application Of Solid State Fermentationmentioning
confidence: 99%
“…Many studies have shown that Solid State Fermentation (SSF) process is more suitable than submerged fermentation (SmF) for obtaining higher enzyme production by filamentous fungi (Viniegra-Gonzalez et al, 2003;Pandey, 2013) and the level of their LMEs production can be further enhanced by supplementing the fermentation medium with various aromatic inducers and metal ions (Elisashvili et al, 2010;Piscitelli et al, 2011;Manavalan et al, 2013;Yang et al, 2013Yang et al, , 2016Kuhar and Papinutti, 2014) which regulate gene expression at the level of transcription Piscitelli et al, 2011). Supplementation of substrate with surfactants has also been explored for increasing enzymes production (Lestan et al, 1993;Zheng and Obbard, 2001;Urek and Pazarlioglu, 2007;Zhang and Cheung, 2011;Usha et al, 2014). They increase the bioavailability of less soluble substrates for the fungus, improve the permeability of cell membrane leading to greater secretion of the extracellular enzyme, enhance enzyme stability and also prevent the denaturation of enzymes during hydrolysis by desorbing them from substrate (Helle et al, 1993;Ahuja et al, 2004;Reddy et al, 1999;Zeng et al, 2006;Liu et al, 2008;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%